Producción bajo riego de cultivares de raigrás perenne (Lolium perenne L.) en Patagonia Norte - Gallego, Juan Jose; Barbarossa, Raul Antonio; Miñon, Daniel Pedro (EEA Valle Inferior, INTA, 2025)
EEA Valle Inferior